PENGARUH KOMITE AUDIT, KUALITAS AUDIT DAN UKURAN PERUSAHAAN TERHADAP INTEGRITAS LAPORAN KEUANGAN: PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023 - Apriyono, Sunia; Amiranto, J. B. (ECONOMOS, 2025)
This study aims to determine the influence of the Audit Committee, Audit Quality and Company Size on the Integrity of Financial Reports (of BUMN Companies listed on the Bursa Efek Indonesia the year 2021-2023 ). This research uses quantitative methods, namely data collection techniques through company annual reports on the official BEI website www.idx.co.id using all 20 samples of state-owned companies. The test results of research that has been carried out through the data collection process, data processing, and data analysis process regarding the influence of the audit committee (X1), audit quality (X2), and company size (X3) on the integrity of financial reports (Y). So it can be concluded that the test results show that data analysis using the t-test (partial) produces the following findings: (1) the audit committee has a partially significant positive influence on the integrity of financial reports (Y) in state-owned companies listed on the BEI for the period 2021- 2023.  (2) audit quality (X2) has a partially significant impact on the integrity of financial reports (Y) in state-owned companies listed on the IDX  the year 2021-2023 .  (3) company size (X3) has a partially significant impact on the integrity of financial reports (Y) in state-owned companies listed on the IDX for the 2021-2023 period.